2016
DOI: 10.1016/j.pjnns.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation or thalamotomy in fragile X-associated tremor/ataxia syndrome? Case report

Abstract: We present the case of a 66-year-old man who has been treated for essential tremor since the age of 58. He developed mild cerebellar gait ataxia seven years after tremor onset. Moderate, global brain atrophy was identified on MRI scans. At the age of 68, only temporary tremor relief could be achieved by bilateral deep brain stimulation of the ventral intermedius nucleus of the thalamus. Bilateral stimulation of the subthalamic nucleus also resulted only in transient improvement. In the meantime, progressive ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Two studies reported no occurrence of AEs. Stimulation frequency varied from 125 to 185 Hz, intensity from 1.5 to 5.4 V, and pulse width from 60 to 150 sec (Table 5) [8388]. …”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported no occurrence of AEs. Stimulation frequency varied from 125 to 185 Hz, intensity from 1.5 to 5.4 V, and pulse width from 60 to 150 sec (Table 5) [8388]. …”
Section: Resultsmentioning
confidence: 99%
“…Here we report the first case of a SCA 27 patient with favorable tremor response to DBS of the VIM and the subthalamic fiber tracts harboring the DTT. To date, a tremor-suppressing effect of high-frequency VIM-DBS was described in SCA 2, 3, 6, 31, and FXTAS ( 11 25 ) ( Table 1 ). Stimulation of subthalamic projections provides the possibility of cerebellar neuromodulation by antidromic stimulation of the DTT ( 4 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration in certain features of the examination performed by the physiotherapist were associated with the progressive nature of FXTAS. This could also be observed during MRI, in the form of an increased signal in T2-weighted image within both hemispheres of cerebellum and bilaterally within middle cerebellar pedunculi, rather than side effects of GK thalamotomy ( 13 ). Approval of the Ethical Committee was not necessary for preparation of this article, as this work is a case study.…”
Section: Case Presentationmentioning
confidence: 99%
“…Non-pharmacological interventions for the treatment of FXTAS include: Deep Brain Stimulation (DBS), Gamma Knife Radiosurgery (GK), Focal Ultrasound (FUS) and Radiofrequency ( 2 13 ) with DBS and Radiofrequency the most popular amongst current literature ( 2 6 , 13 ). With respect to positive outcomes of these treatments, bilateral stimulation with DBS of the ventro-oralis posterior (VOP) thalamic nucleus and zona incerta (ZI) have been documented ( 14 ).…”
Section: Introductionmentioning
confidence: 99%